Hilliard Seigler, M.D. and the origins of kidney transplantation and immunology at Duke - Knechtle, Stuart J.; Barr, Justin (Frontiers in Transplantation, 2023)
The contributions of Dr. Hilliard Seigler to the founding of the Duke kidney transplantation program were considerable in both surgery and immunology. Some of these highlights are summarized based upon interviews with Dr. Seigler by the authors.